2020
DOI: 10.1007/s12350-018-1407-4
|View full text |Cite
|
Sign up to set email alerts
|

Inter-reader variability of SPECT MPI readings in low- and middle-income countries: Results from the IAEA-MPI Audit Project (I-MAP)

Abstract: In this study, inter-observer agreement was moderate-to-good for core group readers and good-to-excellent for expert readers. The quality of reporting is affected by the quality of processing. These results confirm the important role of the IAEA training activities in improving imaging in low- and middle-income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…CT tube voltage validated to work with the attenuation correction algorithm for SPECT reconstruction (Verberne et al 2015) Possibly non-gated images, preferring the average cardiac cycle CT images (Dorbala et al 2013). CT and SPECT FOV should be compatible, meaning that the CT FOV should include the whole thorax.…”
Section: Protocol Standardization For Ct-based Attenuation Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT tube voltage validated to work with the attenuation correction algorithm for SPECT reconstruction (Verberne et al 2015) Possibly non-gated images, preferring the average cardiac cycle CT images (Dorbala et al 2013). CT and SPECT FOV should be compatible, meaning that the CT FOV should include the whole thorax.…”
Section: Protocol Standardization For Ct-based Attenuation Correctionmentioning
confidence: 99%
“…This has motivated the Technologist Committee of the European Association of Nuclear Medicine (EANM) to publish a consensus document emphasizing the competencies in hybrid imaging aiming to set the standards for NMT education in Europe (Fragoso Costa et al 2017). It has been demonstrated that the diagnostic performance in myocardial perfusion imaging (MPI) is highly influenced by image acquisition and processing optimization (Dondi et al 2018), where CT-based attenuation correction (AC) and the coronary artery calcium score (CCS) play a key role in the optimization process of the MPI diagnostic performance. The AC leads to an improvement of the image quality and the CCS has an additive prognostic value (Flotats et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In medical imaging, the interpretation of results can be subjective and influenced by technical factors [ 20 ]. Therefore, it is crucial to optimize and maintain consistent parameters to ensure reliable and meaningful results [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In medical imaging, the interpretation of results can be subjective and influenced by technical factors [ 20 ]. Therefore, it is crucial to optimize and maintain consistent parameters to ensure reliable and meaningful results [ 20 ]. To mitigate potential bias from subjective interpretation and inter-reader variability, we assessed both intraobserver and interobserver agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Another requisite for harmonising procedures in medical imaging is reaching consistent results between different readers, as it affects the comparability of results between different institutions and also among studies performed at different time points, even in the same institution [ 17 ]. Another IAEA study analysed the outcome of IAEA training activities in nuclear cardiology in an international clinical audit on myocardial perfusion imaging [ 18 ]. Participants had to report studies distributed from a core lab.…”
Section: Clinical Audits In Nuclear Medicine Before the Quadrant Projectmentioning
confidence: 99%